Appropriate sample size and effects of microscopic parameters on the shear strength and strain localisation of 2D cohesive-frictional granular assemblies - Kien Trung NGUYEN; Trung Thanh VO; Hoang Nhu NGUYEN (Journal of materials and engineering structures, 2023)
Granular materials are made up of smaller particles, manifestation of microstructure results in a macroscopic response of granular material. Understanding the overall mechanical behaviour from microscopic parameters is one of the main challenges in many engineering fields including civil engineering. When modelling this kind of material by Discrete Element Model (DEM) using idealized circular grains, the effects of appropriate sample size and microscopic parameter changes have been a crucial subject. Previous research has primarily relied on the case of purely frictional granular materials. In this paper, we use DEM to investigate the appropriate sample size and the relationship between microscopic parameters and the macroscopic responses of cohesive-frictional granular assemblies by performing a series of biaxial tests. Our findings indicate that a minimum number of particles is required to balance between mechanical behaviour and computing time. In addition, through extensive parametric studies, the paper explores the impact of factors such as interparticle bonds, intergranular friction coefficients, and initial void index on the overall shear behaviour of granular assemblies. Also, the result reveals a strong correlation between shear band formation and the break field of cohesive contact (static variable) and the translations and rotations of grains (kinematic variable).